ANALISIS FAKTOR PENYEBAB KREDIT MACET PADA USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) DI KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Ardiansyah Hari; Azlina Nur; Desmiyawati Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to test the influences: Character, Economic condition, capacity,Collateral, Time period against non-performing loans to Village’s Save and LendEconomics Businesses (UED-SP) at Rambah Samo Sub-district, Rokan Hulu Regency.The sample in this research totalled 100 Respondents. Method of determination of thesample using the method of accidental sampling. Technique of data analysis in this studyusing multiple linear regression, t-Test and test the assumptions of normality tests includeclassic, multikolonearitas, heteroskedastisitas and autocorrelation data managementusing program SPSS version 25.0 softwere. From the test results prove 1). Character(X1) significant effect partially to the non-performing loans (Y). 2). Economic Condition(X2) significant effect partially to the non-performing loans (Y). 3). Capacity (X3)significant effect partially to the non-performing loans (Y). 4). Collateral (x4) but notsignificant effect partially to the non-performing loans (Y). 5). Time Period (X5)significant effect partially to the non-performing loans (Y).Keywords : Non-Performing Loan, Character, Economic condition, capacity, Collateral,Time period.